2012
DOI: 10.1245/s10434-012-2216-7
|View full text |Cite
|
Sign up to set email alerts
|

Cell Cycle Proteins Predict Recurrence in Stage II and III Colon Cancer

Abstract: Purpose. To investigate the prognostic value of multiple cell cycle-associated proteins in a large series of stage II and III colon cancers. Methods. From formalin-fixed, paraffin-embedded tumor samples of 386 patients with stage II and III colon cancer, DNA was isolated and tissue microarrays were constructed. Tissue microarray slides were immunohistochemically stained for p21, p27, p53, epidermal growth factor receptor, Her2/Neu, b-catenin, cyclin D1, Ki-67, thymidylate synthase, and Aurora kinase A (AURKA).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
68
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(72 citation statements)
references
References 51 publications
(49 reference statements)
3
68
0
Order By: Relevance
“…Many genes and proteins had been uncovered as participated in the development and metastasis of colon cancer, and those genes and proteins also showed correlation with OS of stage III colon cancer patients (Bertagnolli et al, 2009;Ogino et al, 2009;Ogino et al, 2012;Belt et al, 2012). Indeed, the knowledge about those biomacromolecule provide us in-depth understanding about cancers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many genes and proteins had been uncovered as participated in the development and metastasis of colon cancer, and those genes and proteins also showed correlation with OS of stage III colon cancer patients (Bertagnolli et al, 2009;Ogino et al, 2009;Ogino et al, 2012;Belt et al, 2012). Indeed, the knowledge about those biomacromolecule provide us in-depth understanding about cancers.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, neutrophil lymphocyte ratio (NLR), which is thought as an indicator of systemic inflammation (Chiang et al, 2012), also has been reported as a prognostic factor for poor overall survival (OS) in colon cancer patients (Chiang et al, 2012). What's more, correlations between survival and several of genes or proteins, including KRAS (Ogino et al, 2009), BRAF (Ogino et al, 2012, microsatellite instability (Bertagnolli et al, 2009), cell cycle proteins (Belt et al, 2012) and MMP (Wong et al, 2011), were also observed. However, the available published papers still leave some to be desired.…”
Section: Introductionmentioning
confidence: 99%
“…All eligible studies were published between 2005 and 2014. All TNM Stages (I-IV) were considered in 18 studies (46.2%) (9,18,20,27,28,30,(34)(35)(36)(37)(38)40,43,44,50,55,56,58), non-metastatic solid tumors (including Stage I-III or localized disease, based solely on singlestage disease or mixture of tumor stages) were considered in 12 (30.8%) studies (22,29,31,33,39,41,42,46,48,51,53,54); metastatic solid tumors (Stage IV) patients were considered in four studies (10.2%) (23,45,49,57); disease stage was not available were considered in five studies (12.8%). Four studies analyzing AURKA mRNA expression used real-time reverse transcription PCR (RT-PCR) (20,34,35,45); one study analyzing AURKA gene amplification by fluorescence in situ hybridization (FISH) (54); the other one used immunohistochemical (IHC) staining and RT-PCR (47); and the remaining 33 studies applied a immunohistochemistry detection method (9,18,19,21-23,27-33, 36-44,46,48-53,55-58).…”
Section: Characteristics Of Identified Studiesmentioning
confidence: 99%
“…For example, KRAS mutations and specific TP53 mutations are correlated with a relatively poor prognosis (6,7). Low expression of p21 and cyclin D1 and high expression of p53 and AURKA cell-cycle proteins have been correlated with disease recurrences (8). Conversely, patients with MSI tumors have a relatively good prognosis (9).…”
Section: Introductionmentioning
confidence: 99%